THE ROLE OF EAEU LAW IN THE DECARBONIZATION OF ENERGY SYSTEMS OF THE MEMBER STATES AND SUSTAINABLE DEVELOPMENT OF THE GREEN ECONOMY - Tolochko, Ольга Николаевна (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2024)
The article analyzes current problems of improving the rules of law of the EAEU aimed at decarbonizing the energy systems of the member states. The research was carried out using general and special methods of scientific knowledge, including formal-logical, the method of comparative law, etc. It contains proposals for improving the norms of law of the EAEU and the legislation of the Republic of Belarus, in particular, the introduction to the Law of the Republic of Belarus “On Environmental Protection” of 1992 special article 57.1 “Carbon units and carbon market”. The author notes the positive experience of the Republic of Kazakhstan in the field of decarbonization of the economy and concludes that it is advisable to use it in the Republic of Belarus and throughout the EAEU. The expediency of increasing the efficiency of the EAEU integration law is emphasized, including by consolidating the international obligations of the member states in the form of quantitative targets for the introduction of renewable energy sources and for ensuring access to common electrical networks. It is also proposed to establish obligations for Member States to adopt and implement energy efficiency plans, setting targets and reporting on their implementation. According to the author, in order to ensure the implementation of these measures, it is necessary to consolidate decarbonization, the development of renewable energy and increasing energy efficiency as the goals of the EAEU in the Treaty on the EAEU or in a special Appendix to it. The results of the study can be applied in the legislative and law enforcement practice of the EAEU, the Republic of Belarus and other member states of the EAEU.